Biomechanical and Viscoelastic Properties of the Achilles Tendon and Plantar Fascia in Pregnant Women with Pelvic Girdle Pain: A Case–Control Study. (3rd July 2022) - Kablan, Nilüfer; Can, Merve; Ayvacı, Habibe; Gerçek, Nejla; Eroğlu, Zeynep Ayyıldız; Özgit, Berk; Tatar, Yaşar
ABSTRACT: This cross-sectional study examined the biomechanical and viscoelastic properties of the Achilles tendon (AT) and plantar fascia (PF) and analyzed their relationship in pregnant women with pelvic girdle pain (PGP). The study was conducted in a public hospital between January and May 2021. Forty-four pregnant women (PGP+, n: 22; PGP−, n: 22) and 21 non-pregnant women were included. Navicular drop was determined and the tonus, stiffness, and creep of PF and AT were measured by Myometer. Navicular drop was significantly different between the PGP+ and the non-pregnant group in both feet (Right, p = .001; Left, p =< .001), and the PGP− and the non-pregnant group in the left foot ( p = .009). At the right AT, the stiffness was found to be higher in non-pregnant women compared to the PGP+ group ( p = .007). Furthermore, creep was higher in PGP− compared to the non-pregnant group ( p = .016). Tissue properties of PF were similar in all groups ( p > .05). A correlation between tissue properties and the presence of PGP was not found. No findings indicated that the biomechanical and viscoelastic properties of the AT and PF were affected by the physiology of pregnancy. Moreover, no relationship was observed between the presence of PGP and the tissue properties of the AT and PF.